THE INFLUENCE OF SERVICE QUALITY, PRICE, AND FACILITIES ON CUSTOMER SATISFACTION AT COFFEE CAFES IN TANGERANG CITY: Kualitas Pelayanan, Harga, Fasilitas dan Kepuasan konsumen - santi, santi (Journal Civics And Social Studies, 2025)
The coffee shop industry has experienced rapid growth in recent years, creating intense competition among business operators. Customer satisfaction has become a key factor in maintaining loyalty and the sustainability of coffee shop businesses. This study aims to analyze the influence of service quality, price, and facilities on customer satisfaction at coffee cafes in Tangerang City. This research uses a quantitative method with a survey approach. The research sample consists of 103 respondents who are customers of coffee cafes, selected using purposive sampling technique. Data were collected through questionnaires with a 1-5 Likert scale and analyzed using multiple linear regression analysis with the help of SmartPLS 4 software. The research results show that service quality, price, and facilities simultaneously have a significant impact on customer satisfaction at coffee cafes in Tangerang City. These findings imply that coffee shop management needs to prioritize improving service quality through employee training, service responsiveness, and empathy towards customers. In addition, the provision of adequate facilities such as WiFi, comfortable seating, and a conducive atmosphere, as well as competitive pricing that aligns with the value provided, are also important for enhancing customer satisfaction. Further research is recommended to explore other factors such as the café atmosphere, menu variety, and strategic location that can influence customer satisfaction.